Research on Single-Variable Current Perturbation Tracking Method for Maximal Power Tracking Control Method of the Solar Power Generation System - WANG Yu-xin; ZHANG Feng-ge; LI Lin-lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this paper, the traditional grid-connected PV perturbation method of disturbance near the maximum power point about the problems of shock，introduced a method based on single variable current control thought，established grid-connected PV maximum power tracking control system mathematical model, a novel single-variable current perturbation tracking method was put out, as long as the detected output current of the solar panel power generation system can achieve a stable variable maximum power tracking, through simulation and experimental study to verify the correctness of the model and the effectiveness of control methods. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4172